2009
DOI: 10.1111/j.1570-7458.2009.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition preference in the oligophagous tomato fruit fly, Neoceratitis cyanescens

Abstract: We assessed the role of visual and olfactory cues on oviposition preference in the oligophagous tomato fruit fly, Neoceratitis cyanescens (Bezzi) (Diptera: Tephritidae). In a field survey, we evaluated the stage of susceptibility of field‐grown tomatoes by monitoring N. cyanescens infestations from fruit‐setting up to harvest, in relation to post‐flowering time, size, and visual properties of fruit. In two‐choice laboratory experiments, we tested the degree to which females use visual and olfactory cues to sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In dual‐choice experiments on the effects of citrus peel oils and pure chemicals as well, the numbers of eggs laid by females in each oviposition device were compared using the nonparametric Wilcoxon's test for paired samples. The proportions for each treatment when the females exclusively laid eggs in one of the two devices (exclusivity of the response) (Brévault & Quilici, 2009) were analyzed using the G ‐test.…”
Section: Methodsmentioning
confidence: 99%
“…In dual‐choice experiments on the effects of citrus peel oils and pure chemicals as well, the numbers of eggs laid by females in each oviposition device were compared using the nonparametric Wilcoxon's test for paired samples. The proportions for each treatment when the females exclusively laid eggs in one of the two devices (exclusivity of the response) (Brévault & Quilici, 2009) were analyzed using the G ‐test.…”
Section: Methodsmentioning
confidence: 99%
“…Female adults found within the greenhouse and in the plastic traps were more than males. Brevault [7] also observed a majority of female adults in the tomato crop laying eggs.…”
Section: Discussionmentioning
confidence: 92%
“…Adults feed by sucking juices from the underside of the leaf and produce a honey dew which causes leaf darkening. The development cycle from egg to adult takes up to one month [7]. Flies are responsible for severe physiological disorders in tomato, as irregular ripening reported in Culiacan, Mexico [4].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that non-host fruits emitted compounds that inhibit the attraction of tephritid flies to non-host fruits. Few studies have investigated the role of non-host volatiles during the host searching process of tephritid fruit flies (Haisch and Levinson 1980, Linn et al 2005, Brévault and Quilici 2009). For example, Linn et al (2005) found that attraction of Rhagoletis pomonella (Walsh) (Diptera: Tephritidae) originating from apple ( Malus pumila Miller) (Rosales: Rosaceae), hawthorn ( Crataegus spp.…”
Section: Discussionmentioning
confidence: 99%